Music-based interventions to reduce internalizing symptoms in children and adolescents: a meta-analysis - Geipel, Josephine; Koenig, Julian; Hillecke, Thomas; Resch, Franz; Kaess, Michael (Journal of affective disorders, 2018)
Background Existing systematic reviews provide evidence that music therapy is an effective intervention in the treatment of children and adolescents with psychopathology. The objective of the present review was to systematically review and quantify the effects of music-based interventions in reducing internalizing symptoms (i.e., depression and anxiety) in children and adolescents using a meta-analytical approach. Methods Databases and journals were systematically screened for studies eligible for inclusion in meta-analysis on the effects of music-based interventions in reducing internalizing symptoms. A random-effect meta-analysis using standardized mean differences (SMD) was conducted. Results Five studies were included. Analysis of data from (randomized) controlled trials, yielded a significant main effect (Hedge's g = −0.73; 95%CI [−1.42;−0.04], Z = 2.08, p = 0.04, k = 5), indicating a greater reduction of internalizing symptoms in youth receiving music-based interventions (n = 100) compared to different control group interventions (n = 95). Limitations The existing evidence is limited to studies of low power and methodological quality. Included studies were highly heterogeneous with respect to the nature of the intervention, the measurements applied, the samples studied, and the study design. Conclusions Findings indicate that music-based interventions may be efficient in reducing the severity of internalizing symptoms in children and adolescents. While these results are encouraging with respect to the application of music-based intervention, rigorous research is necessary to replicate existing findings and provide a broader base of evidence. More research adopting well controlled study designs of high methodological quality is needed.
Available online: 1 September 2017
Gesehen am 26.04.2018